Analysis of Risk Factors Associated with Measles Incidence in Toddlers in South Halmahera Regency - Abdullah, Syarif; Anggraini, Novita Ana; Peristiowati, Yuly (Journal La Medihealtico, 2025)
Measles is an internal disease (VPD) caused by Morbilivirus. This disease is characterized by the appearance of fever, reddish spots, cough, runny nose, red eyes and rashes all over the body which generally occurs in children. Measles, also known as Morbili or Measles, is a disease caused by the measles virus of the Paramyxovirus group. Transmission can occur through air that has been contaminated by droplets (spit) of an infected person. This case tends to attack early childhood and elementary school age children. Once a person has had measles, he or she will have lifelong immunity to the disease The aim of this research is to determine the factors related to the incidence of measles in toddlers in South Halmahera Regency. The research design used is quantitative research using a "case control" approach. The sampling technique used was purposive sampling with a sample of 106 consisting of 53 case groups and 53 control respondents. Data analysis techniques use Chi Square, Multivariate and Logistic Regression tests. The results of the research show that of the 106 respondents studied, the factors that most influence the incidence of measles in toddlers 0 - 59 months based on the beta value and p value, it is found that the environmental variable has a value < α, namely .021 and the beta value is -1.830, so the variable with the most dominant is the environment. Conclusion. The factors that most influence the occurrence of measles are environmental factors, so it is necessary to conduct socialization or education on the importance of environmental cleanliness to prevent the emergence of measles in children under five.